EFFECTIVENESS OF THE PEACE EDUCATION PROGRAM ON THE SOCIAL AND EMOTIONAL BEHAVIOUR FOR PRE-SCHOOL IN THE SULTANATE OF OMAN - Mahfouda Rashid Al Mushaqiri; Zahari Ishak; Wail Muin Ismail (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The present study aims at providing a peace education program for pre-school children through classroom teaching methods and processes. As peace education is an essential component of good basic education, it is an integral part of UNICEF’s vision of basic education awareness. The Universal Declaration on Education for All (1990) (The Jomtien Declaration) clearly states that basic learning needs are not only essential tools such as literacy and numeracy but also knowledge, skills, attitudes, and values required to live, work with dignity and participate in development. It also states the Inter-Agency Commission, World Conference on Education For All (WCEFA., 1990) that meeting those needs entails responsibility and the promotion of social justice, acceptance of differences, and peace. Furthermore, the present study provided a peace education program (PEP) for pre-school children aged (4 - 6) years in Oman. Where the program contains (28) training sessions are offered within (15) weeks at the rate of one hour per session. The researcher used a scale of two images, the behaviour of the children was measured before and after the experiment, where the researcher adopted the quasi-experimental method, the sample consisted of (40) children in the experimental group and (40) children in the control group. In addition, the results of the current study were in favour of the experimental group, where an improvement in their behaviour was observed after being enrolled in the program. The study finds that pre-school education is very important to spread peace since it focuses on a critical era in children’s life. Thus, the study recommends the ministry of education to consider the findings for a better peaceful learning environment.